Association between unmet social needs and healthy lifestyle parenting behaviors - Egan, Kelsey A.; Luo, Man; Perkins, Meghan; Castro, Ines; Sandel, Megan; Kistin, Caroline J.; Taveras, Elsie M.; Fiechtner, Lauren (Frontiers in Pediatrics, 2023)
Objective: To examine cross-sectional associations of food and housing security risks and healthy lifestyle parenting behaviors related to nutrition and physical activity among families with children with overweight/obesity. Methods: We surveyed 407 parents of children ages 6-12 years with overweight/obesity. Exposures were measures of food and housing insecurity risk. Outcomes were healthy lifestyle parenting behaviors related to nutrition and physical activity. Logistic regression models for each exposure-outcome relationship were adjusted for parental educational attainment, parental cohabitation status, household size, and household income. Results: In multivariable-adjusted models, food insecurity was associated with significantly lower odds of parent modeling exercise [aOR 0.60 (95% confidence interval (CI): 0.37, 0.96)] and parent modeling eating healthy foods [aOR 0.42 (95% CI: 0.24, 0.73)]. Housing insecurity was associated with significantly lower odds of parent modeling exercise [aOR 0.57 (95% CI: 0.35, 0.95)]. Conclusions: Food insecurity and housing insecurity may be barriers to parents adopting and modeling healthy lifestyle parenting behaviors related to physical activity and nutrition.